Mediport use as an acceptable standard for CAR T cell infusion - Eylon, Maya; Prabhu, Snehit; John, Samuel; King, Maxwell J. M.; Bhatt, Dhruv; Curran, Kevin J.; Erickson, Courtney; Karras, Nicole A.; Phillips, Christine L.; Satwani, Prakash; Hermiston, Michelle; Southworth, Erica; et al. (Frontiers in Immunology, 2023)
Mediport use as a clinical option for the administration of chimeric antigen receptor T cell (CAR T cell) therapy in patients with B-cell malignancies has yet to be standardized. Concern for mediport dislodgement, cell infiltration, and ineffective therapy delivery to systemic circulation has resulted in variable practice with intravenous administration of CAR T cell therapy. With CAR T cell commercialization, it is important to establish practice standards for CAR T cell delivery. We conducted a study to establish usage patterns of mediports in the clinical setting and provide a standard of care recommendation for mediport use as an acceptable form of access for CAR T cell infusions. In this retrospective cohort study, data on mediport use and infiltration rate was collected from a survey across 34 medical centers in the Pediatric Real-World CAR Consortium, capturing 504 CAR T cell infusion routes across 489 patients. Data represents the largest, and to our knowledge sole, report on clinical CAR T cell infusion practice patterns since FDA approval and CAR T cell commercialization in 2017. Across 34 sites, all reported tunneled central venous catheters, including Broviac® and Hickman® catheters, as accepted standard venous options for CAR T cell infusion. Use of mediports as a standard clinical practice was reported in 29 of 34 sites (85%). Of 489 evaluable patients with reported route of CAR T cell infusion, 184 patients were infused using mediports, with no reported incidences of CAR T cell infiltration. Based on current clinical practice, mediports are a commonly utilized form of access for CAR T cell therapy administration. These findings support the safe practice of mediport usage as an accepted standard line option for CAR T cell infusion.